The Effect of Lifting Speed on Cumulative and Peak Biomechanical Loading for Symmetric Lifting Tasks - Kasey O. Greenland; Andrew S. Merryweather; Donald S. Bloswick (Elsevier, 2013)
Background: To determine the influence of lifting speed and type on peak and cumulative back compressive force (BCF) and shoulder moment (SM) loads during symmetric lifting. Another aim of the study was to compare static and dynamic lifting models. Methods: Ten male participants performed a floor-to-shoulder, floor-to-waist, and waist-to-shoulder lift at three different speeds [slow (0.34 m/s), medium (0.44 m/s), and fast (0.64 m/s)], and with two different loads [light (2.25 kg) and heavy (9 kg)]. Two-dimensional kinematics and kinetics were determined. A three-way repeated measures analysis of variance was used to calculate peak and cumulative loading of BCF and SM for light and heavy loads. Results: Peak BCF was significantly different between slow and fast lifting speeds (p < 0.001), with a mean difference of 20% between fast and slow lifts. The cumulative loading of BCF and SM was significantly different between fast and slow lifting speeds (p < 0.001), with mean differences ≥80%. Conclusion: Based on peak values, BCF is highest for fast speeds, but the BCF cumulative loading is highest for slow speeds, with the largest difference between fast and slow lifts. This may imply that a slow lifting speed is at least as hazardous as a fast lifting speed. It is important to consider the duration of lift when determining risks for back and shoulder injuries due to lifting and that peak values alone are likely not sufficient.